2017
DOI: 10.1038/srep46641
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of inhibition of lipid-linked oligosaccharide flippase PglK by a conformational nanobody

Abstract: PglK is an ABC transporter that flips a lipid-linked oligosaccharide (LLO) that serves as a donor in protein N-glycosylation. Previous structures revealed two inward-facing conformations, both with very large separations of the nucleotide binding domains (NBDs), and a closed, ADP-bound state that featured an occluded cavity. To investigate additional states, we developed conformation-sensitive, single-domain camelid nanobodies (Nb) and studied their effect on PglK activity. Biochemical, structural, and mass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 46 publications
1
30
0
1
Order By: Relevance
“…Molecular clamping of the closed extracellular gate was also achieved by a cyclic peptide raised against CmABCB1 19 . Further examples of binders that prevent the IF-OF conversion are nanobodies raised against ABCB1 and PglK, which both sterically clash with NBD closure 20,21 . In contrast, our binders are specific for the OF state and consequently impede the OF-IF conversion.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular clamping of the closed extracellular gate was also achieved by a cyclic peptide raised against CmABCB1 19 . Further examples of binders that prevent the IF-OF conversion are nanobodies raised against ABCB1 and PglK, which both sterically clash with NBD closure 20,21 . In contrast, our binders are specific for the OF state and consequently impede the OF-IF conversion.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins mediating this process are passive or active transporters. Well-studied examples include the calcium-activated nhTMEM16 scramblase that catalyzes the shuffling of lipids between the inner and outer leaflets of the bilayer (Bethel and Grabe, 2016;Brunner et al, 2014); the flippase MurJ (Kuk et al, 2017), which catalyzes the translocation of the peptidoglycan building block undecaprenyl-diphosphate-MurNAcpentapeptide-GlcNAc (lipid II) in bacteria; type IV P-type ATPases (Lopez-Marques et al, 2014;Vestergaard et al, 2014), which are ATP-driven transporters that catalyze the translocation of phospholipids from the exoplasmic to the cytosolic leaflet of cell membranes; the ATP binding cassette (ABC) flippase MsbA (Mi et al, 2017;Ward et al, 2007), an essential inner membrane transporter in Gram-negative bacteria that exports lipid A core (Doshi and van Veen, 2013;Eckford and Sharom, 2010); and the ABC flippase PglK (Perez et al, 2015(Perez et al, , 2017 that translocates the lipid-linked oligosaccharide (LLO) undecaprenyl-diphosphate-BacGalNAc 5 Glc, essential for bacterial protein N-glycosylation in the human pathogen Campylobacter jejuni (Alaimo et al, 2006). A similar LLO translocation process occurs in the endoplasmic reticulum membrane, where the LLO Man 5 GlcNAc 2 -PP-dolichol is flipped from the cytosolic side to the luminal side; however, the nature of the responsible flippase remains elusive (Burda and Aebi, 1999;Helenius et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanism of translocation is still unknown, the crystal structure of PglK flippase contains a salt bridge cluster that suggests a hypothetical translocation intermediate containing a charge-stabilized buried lipid head group. A large conformational change is required for flippase activity, as demonstrated by the inhibition of its function by a cross-binding nanobody [39] In other studies, it was experimentally demonstrated that same side positioning of multiple Arg or His on a transmembrane α-helix was sufficient to generate flippase activity, using only short peptides [40]. The crystal structure of MurJ flippase (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%